The role of pleuroscopy in undiagnosed exudative pleural effusion - Prabhu, V. G. (Medknow Publications & Media Pvt Ltd, 2012)
AIMS: To find the diagnostic yield of a pleuroscopic pleural biopsy and to find the complication rates. SETTINGS AND DESIGN: Institutional based prospective study. MATERIALS AND METHODS: Sixty-eight consecutive patients who had undiagnosed exudative pleural effusion were recruited for pleuroscopy from September 2007 to August 2010. RESULTS: A total of 68 patients (55 males and 13 females; mean age 49 years) underwent pleuroscopy. Malignancy was diagnosed in 24 patients, 22 patients had non-specific inflammation, tuberculosis was found in 16 patients, empyema was found in 2 patients, 1 patient had sarcoidosis, 1 patient had normal pleura and it was non-diagnostic in 2 patients. The diagnostic yield was 97%. There were no major complications, only four patients had minor complication like subcutaneous emphysema (three patients) and prolonged air leak (one patient). CONCLUSIONS: Pleuroscopy is a safe, simple, and valuable tool in the diagnosis of undiagnosed exudative pleural effusion with minimal complication rates.